2018
DOI: 10.1038/s41593-018-0168-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct pericyte-to-neuron reprogramming via unfolding of a neural stem cell-like program

Abstract: Ectopic expression of defined transcription factors can force direct cell-fate conversion from one lineage to another in the absence of cell division. Several transcription factor cocktails have enabled successful reprogramming of various somatic cell types into induced neurons (iNs) of distinct neurotransmitter phenotype. However, the nature of the intermediate states that drive the reprogramming trajectory toward distinct iN types is largely unknown. Here we show that successful direct reprogramming of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 55 publications
4
91
0
Order By: Relevance
“…Demonstration of the endogenous reprogrammability (trans‐differentiation) of pericytes to generate various interneurons was an important aspect of the current study. The reprogrammability of pericytes is consistent with a recent report on forced ectopic expression of Ascl1 and Sox2 that triggers direct conversion of pericytes into interneurons (Karow et al, ). The dormant neurogenic capacity of microvascular pericytes can be traced back to the developmental origin of these cells.…”
Section: Discussionsupporting
confidence: 90%
“…Demonstration of the endogenous reprogrammability (trans‐differentiation) of pericytes to generate various interneurons was an important aspect of the current study. The reprogrammability of pericytes is consistent with a recent report on forced ectopic expression of Ascl1 and Sox2 that triggers direct conversion of pericytes into interneurons (Karow et al, ). The dormant neurogenic capacity of microvascular pericytes can be traced back to the developmental origin of these cells.…”
Section: Discussionsupporting
confidence: 90%
“…Neuroregeneration in adult mammalian CNS has been proved to be one of the most difficult tasks in the entire regenerative medicine field, largely because neurons cannot divide to regenerate themselves and external cell transplantation yields very low number of functional new neurons (Goldman, 2016). To overcome the limitations of cell transplantation therapy, we, together with other research groups, have developed in vivo cell conversion technology to regenerate functional new neurons from endogenous glial cells for brain repair (Chen et al, 2019; Gascon et al, 2016; Guo et al, 2014; Karow et al, 2018; Liu et al, 2015; Niu et al, 2015; Niu et al, 2018; Pereira et al, 2017; Torper et al, 2015; Wang et al, 2016; Zhang et al, 2018). While stab injury model has been commonly used in various in vivo cell conversion studies, we have previously demonstrated in a mouse Alzheimer’s disease model that NeuroD1 can convert reactive astrocytes into functional neurons in 14-month old AD mouse brains (Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent conversion strategies using BAM, Ascl1/ Ngn2, and miR-9/9*-124 typically give rise to a major population of excitatory glutamatergic neurons, and the Ngn2-only protocols lead to excitatory cholinergic neurons ( Fig. Ascl1/Sox2-based iNs generated from pericytes in vivo resemble mixed GABAergic/glutamatergic cultures [69], and Ascl1 has been shown to induce oligodendroglial cells from adult neural stem cells in the dentate gyrus of mice [70]. While these observations somewhat imply a glutamatergic-by-default mechanism, or alternatively have led to the assumption that Ascl1 and Ngn2 are pro-glutamatergic and pro-cholinergic, respectively, reality appears less straightforward.…”
Section: Subtype-specific In Conversionmentioning
confidence: 99%
“…For example, iNs generated from iPSCs through Ngn2-only protocols are predominantly glutamatergic [16,68]. Ascl1/Sox2-based iNs generated from pericytes in vivo resemble mixed GABAergic/glutamatergic cultures [69], and Ascl1 has been shown to induce oligodendroglial cells from adult neural stem cells in the dentate gyrus of mice [70]. Also, both TFs are involved in midbrain and hindbrain neuronal differentiation and have varying capacities depending on the regional context [71,72].…”
Section: Subtype-specific In Conversionmentioning
confidence: 99%
See 1 more Smart Citation